Al-Mu'tazila Before Caliph Al-Ma'mun's Era - Alesa, Mohammad; Aldafheeri, Khaled (European Scientific Journal, ESJ, 2016)
Scholars in Al-Mu'tazila, and the dilemma of creating Qur'an that relates to it, was being used in studying various issues that is connected with the Abbasid caliphate Al-Ma'mun. This was without any deep search of its roots of more than a century before AL-Ma'mun's era. In this study titled â€œAl-Mu'tazila before Caliph Al-Ma'mun's era,â€ we attempt to trace the initial precursors (I'tezal/seclusion), starting by AL-Qadariya which emerged as a reaction from Umayyad Jabriya to reaching Al-Ma'mun's taking power.